Spectroscopy and Conductivity Studies of Polyvinyl Alcohol (PVA)/Polypyrrol (Ppy) Nanocomposite with Various Chloride Metals to Improved Properties of the Polymers - Shahin, Naglaa; Abd El Hamid, Reham Kamal (JOURNAL OF ADVANCES IN PHYSICS, 2019)
Polyvinyl alcohol- polypyrrole (PVA-PPy) nanocomposites with metal chlorides (FeCl3, NiCl2, CuCl2 and ZnCl2) have been synthesized by chemical oxidative polymerization method. These synthesized nanocomposites are characterized by using FTIR, X-ray diffraction, Transition electron microscope (TEM) and Conductivity measurement. TEM exhibit that all of the composites have uniform sizes and morphologies. The diameter of PVA/PPy nanocompsite is 58nm when the metals added to the PVA/PPy the diameters becomes smaller. The variation of electrical conductivity (log ?) with 1000/T for PVA/PPy nanocomposite with metal chlorides revealed that the increase in conductivity s at temperature (393K) with added metals can be attributed to the creation of induced charge carriers in PVA/PPy matrix